Crecimiento y escalamiento en la producción del nemátodo Turbatrix aceti (Brunn, 1949), para su utilización en larvicultura del pez blanco (Chirostoma estor) - Ahumada García, Alejandra (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
Nematodes are live feed with potential for aquaculture, due to their rapid rates of reproduction, wide range of small sizes, from less than 10 ?m up to 2 mm, and potential for enrichment (Brüggemann, 2012). Turbatrix aceti is a free-living nematode and can swim actively and remain suspended in the water column, being this advantageous aspect for its use as live food in aquatic systems. Growing media for the nematodes can be solid or liquid, being the last one more versatile. The nematode T. aceti may be kept in a liquid basic medium (BM) consisting of vinegar and apple. However growth of T. aceti can be improved by the formulation of an artificial diet (DA) that exceeds the MB and allows scaling in the nematode production for hatcheries. The pescado blanco Chirostoma estor, an endemic silverside from Lake of Pátzcuaro, located in the State of Michoacán and it is an ancestral food source for Purepechas and mestizo communities of that region. Due to the environmental degradation of the ecosystem, to its high demand and prices in the local and regional market, wild populations of this species have declined in the Lake (RNP, 2008). This status evidenced the need to learn about the basics for C. estor aquaculture, feeding preferences and habits, the influence of environmental factors on the development and survival, Larval feeding, weaning and balanced diets (Martinez-Palacios et al., 2002). One of the critical stages in the life cycle of fish is the larval stage because during this the resorption of the yolk sac and the on setting of autotrophy takes place (Hoffer and Nassir-Udinn, 1985;) Jones and Hude, 1986; Kolkovski et al., 1993; Watanabe and Kiron, 1994) larvae must have a surce of feed that provides them essential nutrients to meet all its energy requirements for growth and survival, as well as been atractive enough an in an appropriate size to be able to be consumed by the small-mouthed larvae.

Los nematodos constituyen un alimento vivo con potencial, debido a sus rápidas tasas de reproducción, pequeño tamaño y posibilidad de enriquecimiento (Brüggemann, 2012). Turbatrix aceti es el único nemátodo que se mantiene suspendido en la columna de agua, siendo ventajoso para su utilización en sistemas acuáticos. Los medios para crecimiento de nemátodos pueden ser sólidos o líquidos. T. aceti puede ser mantenido en una dieta base (DB) líquida con vinagre y manzana. El crecimiento de T. aceti puede mejorar al formular una dieta artificial (DA) que permita su escalamiento. El pez blanco (Chirostoma estor) es una especie endémica al Lago de Pátzcuaro en el estado de Michoacán, y fuente alimenticia ancestral para las comunidades Purépechas de dicha región. Debido al deterioro ambiental, a su elevada demanda y precios en el mercado , las poblaciones silvestres de dicha especie han declinado (RNP, 2008). A partir de eso surge la necesidad de investigar aspectos básicos para la acuicultura de C. estor (Martínez-Palacios et al., 2002). Una etapa crítica en el ciclo de vida de los peces es la larvaria debido a que durante ésta se presenta la reabsorción del saco vitelino e inicio de la autotrofía (alimentación exógena) (Hoffer y Nassir-Udinn, 1985; Jones y Hude, 1986; Kolkovski et al., 1993; Watanabe y Kiron, 1994) Las larvas deben contar con un alimento que les provea los nutrientes esenciales para cubrir sus requerimientos energéticos para el crecimiento y supervivencia, así como un tamaño adecuado para ser consumido. En la acuicultura de C. estor, y similar a lo que sucede en los peces marinos, se presenta una baja supervivencia en las etapas tempranas de desarrollo (Martínez- Palacios, 2002).
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; IIAF-M-2016-0365; Alimento vivo; Nemátodos; Dieta artificial; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1895